The Study of lithic assemblages on deflation surfaces. The case study of Arroyo Verde, Northern Patagonia coast, Argentina - Carranza, Eugenia (2018)
This paper focuses on surface lithic artefacts from Holocene coastal hunter gatherer occupations of Arroyo Verde archaeological locality (Rio Negro province, Northern Patagonia, Argentina). The study of lithic assemblages collected at a deflation surface surrounded by stabilised sand dunes near the coastline, shows that wind produce significant corrasion (wind abrasion) of artefacts and affects preservation of small and medium size artefacts. The sample is mainly composed of chert knapping debitage with abraded and polished edges and surfaces. The artefact size distribution suggests that a subset of the assemblage exhibits good preservation, possibly due to the recent subaerial exposure. Furthermore, carbonate and mould coatings were recorded over the artefacts surface in contact with the ground, which indicates the presence of humid conditions in the sand dunes deflation area. In order to explore the factors that affected assemblage stability conditions in the locus, a machine learning based decision tree was applied. The model predicts and defines a threshold at which the occurrence of instability conditions may appear. Also, it suggests that relative altitude of artefacts within the deflation hollow is the primary variable explaining the exposure conditions recorded in the artefacts and it points out processes of differential deflation over time. The data presented here illustrates how wind alters local surface materials and emphasizes that a taphonomic perspective is needed to assess the formation processes within northern Patagonia coastal archaeological assemblages.